GANGGUAN FUNGSI MOTOR PADA PENDERITA HIPERTENSI - Darwin Amir* (NEURONA, 2010)
INTRODUCTIONTHE PREVALENCE OF HYPERTENSION TENDED TO INCREASE IN WHICH THE ADULT POPULATIONS WITH HYPERTENSION REACH 266 FOR MEN AND 261 FOR WOMEN AND IS PROJECTED IN 2025 TO 290 FOR MEN AND 295 FOR WOMEN GLOBAL BURDEN HYPERTENSION WORLDWIDE DATA ANALYSIS 2000 HYPERTENSION IS KNOWN AS RISK FACTORS FOR CEREBROVASCULAR DISEASE CVD WHICH CAN CAUSE PARALYSIS DISABILITYBEFORE THE COMPLICATIONS OF CVD AT THE PRE PATHOGENESIS STAGE OF HYPERTENSION CAN CAUSE NERVOUS SYSTEM DISORDERS OR PREMATURE DISABILITY THAT MAY AFFECT THE ABILITY TO PERFORM DAILY ACTIVITIES